Resveratrol reduces renal and lung injury caused by sepsis in rats - ŞENER, GÖKSEL; ÇETİNEL, ŞULE (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2006)
Resveratrol (3,5,4'-trans-trihydroxystilbene), a natural phytoalexin, has various pharmacological effects, including anti-inflammatory properties via inhibition of oxidation, leukocyte priming, and expression of inflammatory mediators. The present study was aimed to investigate the possible beneficial activities of resveratrol on lung and kidney damage in a rat model of sepsis. Materials and methods. Sepsis was induced to Sprague-Dawley rats of both sexes (200-250 g) by cecal ligation and perforation. The rats were treated with resveratrol (30 mg/kg; i.p.) or saline after induction of sepsis and at 16 h. Twenty-four hours after the sepsis-induction, all rats were decapitated. Blood was collected for the measurement of tumor necrosis factor-a level and lactate dehydrogenase activity. Lung and kidney samples were taken for histological assessment and for the measurement of malondialdehyde, glutathione level, myeloperoxidase activity, and collagen content. Results. Sepsis caused a significant increase in malondialdehyde levels, myeloperoxidase activity, and collagen content of the lung and kidney tissues with a concomitant reduction in glutathione levels. Microscopic examination revealed severe destruction of regular morphology in both lung and kidney tissues. Serum tumor necrosis factor-a and lactate dehydrogenase levels also were higher in rats with sepsis compared to those of the sham group. Resveratrol treatment reversed these biochemical parameters and preserved tissue morphology as evidenced by histological evaluation. Conclusions. Resveratrol, a phenolic compound, reduces sepsis-induced remote organ injury, at least in part, through its ability to balance oxidant-antioxidant status, to inhibit neutrophil infiltration and to regulate the release of inflammatory mediators. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: sepsis; antioxidant; kidney; lung; rat; resveratrol; WINE CONSTITUENT POLYPHENOL; RED WINE; INFLAMMATION; DAMAGE; ISCHEMIA/REPERFUSION; CARDIOPROTECTION; ANTIOXIDANTS; PERITONITIS; GLUTATHIONE; EXPRESSION